Oxidation of Aqueous Phosphorous Acid Electrolyte in Contact with Pt Studied by X-ray Photoemission Spectroscopy - Wibowo, Romualdus Enggar; Garcia-Diez, Raul; Bystron, Tomas; Prokop, Martin; van der Merwe, Marianne; Arce, Mauricio D.; Jiménez, Catalina E.; Hsieh, Tzung En; Frisch, Johannes; Steigert, Alexander; Favaro, Marco; Starr, David E.; et al. (ACS Applied Materials and Interfaces, 2023)
The oxidation of the aqueous H3PO3 in contact with Pt was investigated for a fundamental understanding of the Pt/aqueous H3PO3 interaction with the goal of providing a comprehensive basis for the further optimization of high-temperature polymer electrolyte membrane fuel cells (HT-PEMFCs). Ion-exchange chromatography (IEC) experiments suggested that in ambient conditions, Pt catalyzes H3PO3 oxidation to H3PO4 with H2O. X-ray photoelectron spectroscopy (XPS) on different substrates, including Au and Pt, previously treated in H3PO3 solutions was conducted to determine the catalytic abilities of selected metals toward H3PO3 oxidation. In situ ambient pressure hard X-ray photoelectron spectroscopy (AP-HAXPES) combined with the “dip-and-pull” method was performed to investigate the state of H3PO3 at the Pt|H3PO3 interface and in the bulk solution. It was shown that whereas H3PO3 remains stable in the bulk solution, the catalyzed oxidation of H3PO3 by H2O to H3PO4 accompanied by H2 generation occurs in contact with the Pt surface. This catalytic process likely involves H3PO3 adsorption at the Pt surface in a highly reactive pyramidal tautomeric configuration.
CRIS-Team Scopus Importer:2023-12-08
Keywords: aqueous H; HT-PEMFCs; in situ AP-HAXPES; ion-exchange chromatography; Pt/H; Pt|aqueous H